2017
DOI: 10.1016/j.celrep.2016.12.077
|View full text |Cite
|
Sign up to set email alerts
|

Arginine Deprivation Inhibits the Warburg Effect and Upregulates Glutamine Anaplerosis and Serine Biosynthesis in ASS1-Deficient Cancers

Abstract: SUMMARYTargeting defects in metabolism is an underutilized strategy for the treatment of cancer. Arginine auxotrophy resulting from the silencing of argininosuccinate synthetase 1 (ASS1) is a common metabolic alteration reported in a broad range of aggressive cancers. To assess the metabolic effects that arise from acute and chronic arginine starvation in ASS1-deficient cell lines, we performed metabolite profiling. We found that pharmacologically induced arginine depletion causes increased serine biosynthesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
162
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(177 citation statements)
references
References 52 publications
(80 reference statements)
10
162
1
Order By: Relevance
“…Tumor cells re-acquire de novo arginine biosynthesis capabilities by ASS1 re-expression [73,77]. It is worth noting that metabolic changes are mostly negligible between ADI-PEG20 treated and untreated cells, providing further evidence for resistance development.…”
Section: Intrinsic and Acquired Resistance Mechanisms Towards Adimentioning
confidence: 89%
See 3 more Smart Citations
“…Tumor cells re-acquire de novo arginine biosynthesis capabilities by ASS1 re-expression [73,77]. It is worth noting that metabolic changes are mostly negligible between ADI-PEG20 treated and untreated cells, providing further evidence for resistance development.…”
Section: Intrinsic and Acquired Resistance Mechanisms Towards Adimentioning
confidence: 89%
“…Finally, Kremer et al identified a treatment-related switch from dependence on aerobic glycolysis (the Warburg effect) to glutamine anaplerosis and mitochondrial oxidative phosphorylation [73]. The Warburg effect is imperative in providing rapidly proliferating cells with pyruvate as an electron acceptor, necessary in the oxidative biosynthesis of aspartate.…”
Section: Stress Responses Upon Adi-based Therapy -Autophagy Senescenmentioning
confidence: 99%
See 2 more Smart Citations
“…5,6 One of the many alterations of metabolic pathways that occur upon short-term ADI-PEG20 treatment was the significant redirection of cellular glucose. While cancer cells typically ferment the majority of cellular glucose into lactic acid and oxidize lesser amounts via the TCA cycle, ADI-PEG20 caused a decrease in the flux of glucose-derived carbons into both lactate and TCA cycle intermediates.…”
mentioning
confidence: 99%